Pengaruh 4 Pilar Rasio Keuangan terhadap Pertumbuhan Laba: Studi pada Industri Makanan & Minuman di BEI 2020-2024 - Amalia Popy Novariyanti; Jaka Waskito; Niken Wahyu Cahyaningtyas (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study examines the influence of current ratio, debt-to-equity ratio, return on assets, and total asset turnover on profit growth within Indonesia Stock Exchange-listed Food & Beverage subsector firms (2020-2024). This study aims to examine the impact of current ratio, debt-to-equity ratio, return on assets (ROA), and total asset turnover (TATO) on profit growth. The population comprised 95 registered entities, with 33 companies selected via purposive sampling meeting inclusion criteria. Secondary quantitative data were collected through annual financial report documentation. Analytical methods included descriptive statistics, classical assumption testing, multiple linear regression, partial t-tests, simultaneous f-tests, and coefficient of determination analysis using SPSS 27. Results demonstrate: Current ratio and debt-to-equity ratio negatively affect profit growth, Return on assets positively influences profit growth, Total asset turnover has no significant impact, Collectively, the four ratios significantly explain 24.9% of profit growth variability, while external factors dominate the remaining variance.